Beta-cell hubs maintain Ca2+ oscillations in human and mouse islet simulations. Issue 4 (4th July 2018) - Lei, Chon-Lok; Kellard, Joely A.; Hara, Manami; Johnson, James D.; Rodriguez, Blanca; Briant, Linford J.B.
ABSTRACT: Islet β-cells are responsible for secreting all circulating insulin in response to rising plasma glucose concentrations. These cells are a phenotypically diverse population that express great functional heterogeneity. In mice, certain β-cells (termed 'hubs') have been shown to be crucial for dictating the islet response to high glucose, with inhibition of these hub cells abolishing the coordinated Ca 2+ oscillations necessary for driving insulin secretion. These β-cell hubs were found to be highly metabolic and susceptible to pro-inflammatory and glucolipotoxic insults. In this study, we explored the importance of hub cells in human by constructing mathematical models of Ca 2+ activity in human islets. Our simulations revealed that hubs dictate the coordinated Ca 2+ response in both mouse and human islets; silencing a small proportion of hubs abolished whole-islet Ca 2+ activity. We also observed that if hubs are assumed to be preferentially gap junction coupled, then the simulations better adhere to the available experimental data. Our simulations of 16 size-matched mouse and human islet architectures revealed that there are species differences in the role of hubs; Ca 2+ activity in human islets was more vulnerable to hub inhibition than mouse islets. These simulation results not only substantiate the existence of β-cell hubs, but also suggest that hubs may be favorably coupled in the electrical and metabolic network of the islet, and that targeted destruction of these cells would greatly impair human islet function.